2015
DOI: 10.1111/febs.13598
|View full text |Cite
|
Sign up to set email alerts
|

Cell death induced by endoplasmic reticulum stress

Abstract: The endoplasmic reticulum (ER) is an organelle with multiple functions. The synthesis of transmembrane proteins and proteins that are to be secreted occur in this organelle. Many Author ManuscriptThis article is protected by copyright. All rights reserved conditions that impose stress to the cells, including hypoxia, starvation, infections and changes in secretory needs challenge the folding capacity of the cell and promote ER stress. The cellular response involves the activation of sensors that transduce sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
654
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(711 citation statements)
references
References 77 publications
10
654
0
4
Order By: Relevance
“…18) In contrast, the PERK/ATF6 branches are involved in the induction of cell death. 19) Therefore, these signals may be implicated in the MeHg-induced loss of cell viability. To determine this possibility, we tested the effect of a PERKspecific inhibitor (GSK2606414) on MeHg-induced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…18) In contrast, the PERK/ATF6 branches are involved in the induction of cell death. 19) Therefore, these signals may be implicated in the MeHg-induced loss of cell viability. To determine this possibility, we tested the effect of a PERKspecific inhibitor (GSK2606414) on MeHg-induced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…BIM is an important mediator of tumor cell death (15). Other studies have previously demonstrated that several kinase-driven tumors, including chronic myelogenous leukemia and NSCLC, maintain a survival advantage by suppressing BIM transcription and by targeting BIM protein for proteasomal degradation (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…BIM is expressed in a wide variety of tissues, including GC, and acts as a pivotal regulator of the mitochondrial apoptosis pathway (14). Abnormal levels of BIM have been recognized to affect the chemotherapy response (15). Platinum-resistant cancer cells conserved sensitivity to BH3-induced mitochondrial apoptosis (16).…”
Section: Introductionmentioning
confidence: 99%
“…When there are too many unfolded or misfolded proteins accumulated in the ER, the ER becomes stressed and the so-called unfolded protein response (UPR) is activated [2][3][4]. The UPR aims to alleviate ER stress through blocking protein synthesis and activating the expression of chaperone genes, whereas prolonged UPR could induce cell death [5,6].…”
Section: Introductionmentioning
confidence: 99%